2023
DOI: 10.3390/f14122449
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic and Microscopic Anatomical Characteristics of Six Korean Oak Species

Alvin Muhammad Savero,
Jong-Ho Kim,
Byantara Darsan Purusatama
et al.

Abstract: The macroscopic and microscopic anatomical characteristics of wood impact its utilization. This study investigated and compared the anatomical characteristics of six Korean oak wood species: Quercus variabilis, Quercus serrata, Quercus mongolica, Quercus dentata, Quercus aliena, and Quercus acutissima. Microscopic anatomical characteristics were evaluated according to the International Association of Wood Anatomists’ list for hardwood identification. Q. variabilis had a corky bark texture, with a color similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The radial variation pattern of fiber length in our study is consistent with those in previous studies on Quercus spp. [32][33][34][35]. The authors mentioned that the fiber length of Quercus spp.…”
Section: Fiber Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The radial variation pattern of fiber length in our study is consistent with those in previous studies on Quercus spp. [32][33][34][35]. The authors mentioned that the fiber length of Quercus spp.…”
Section: Fiber Lengthmentioning
confidence: 99%
“…To date, there have been few comparative studies on the anatomical characteristics of the six Korean oak species. In a previous study, we reported a comparative analysis of macroscopic and microscopic anatomical features of six Korean oak wood species [35]. However, the information on the quantitative anatomical characteristics is crucial to completing the identification keys for these species.…”
Section: Introductionmentioning
confidence: 99%